2014
DOI: 10.1085/jgp.1434oia12
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity regulates extracellular tau in vivo

Abstract: Tau is primarily a cytoplasmic protein that stabilizes microtubules. However, it is also found in the extracellular space of the brain at appreciable concentrations. Although its presence there may be relevant to the intercellular spread of tau pathology, the cellular mechanisms regulating tau release into the extracellular space are not well understood. To test this in the context of neuronal networks in vivo, we used in vivo microdialysis. Increasing neuronal activity rapidly increased the steady-state level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 17 publications
7
78
0
Order By: Relevance
“…Numerous studies have linked AD-pathology and symptomology to disrupted functional coupling of cortical regions [85,86] resulting in cognitive dysfunction [23,87]. In support of the disconnection hypothesis, we found functional decoupling between the vmPFC and posterior parietal regions, which is further supported by the different network hierarchies we found in prodromal AD compared to SCD and HC.…”
Section: Disrupted Functional Coupling Of Prefrontal and Parietal Dmnsupporting
confidence: 85%
“…Numerous studies have linked AD-pathology and symptomology to disrupted functional coupling of cortical regions [85,86] resulting in cognitive dysfunction [23,87]. In support of the disconnection hypothesis, we found functional decoupling between the vmPFC and posterior parietal regions, which is further supported by the different network hierarchies we found in prodromal AD compared to SCD and HC.…”
Section: Disrupted Functional Coupling Of Prefrontal and Parietal Dmnsupporting
confidence: 85%
“…Reports that early Aβ deposition occurs preferentially in regions of high neuronal activity [170] and that secretion of Aβ is driven by synaptic activity [e.g., 171] suggests diffusion of extracellular glutamate to neighboring synapses could facilitate the spread of Aβ pathology. Similarly, recent work suggests presynaptic glutamate release is sufficient to drive tau release into the extracellular space [172]. Thus, glutamate-mediated exocytosis of tau may indicate one mechanism for the trans-synaptic spread of tau pathology associated with synaptic activity.…”
Section: Future Directionsmentioning
confidence: 92%
“…Other studies have shown that release of Tau monomer is increased by synaptic activity (50,51). It remains unknown, however, whether trans-synaptic movement of aggregates is activity-dependent or whether it simply results from release of aggregated material at the axon terminal, where it is taken up by neighboring cells.…”
Section: Prion-like Propagation Of Protein Pathologymentioning
confidence: 99%